Produksi Bioetanol dari Ampas Sorgum Lahan Kering dengan Perlakuan Awal Microwave Irradiasi - Sefrinus MD Kolo; Yuni Sine (Fakultas Pertanian, Universitas Timor, 2019)
One potential ingredient that has a high starch content is sorghum (Sorghum bicolor L.). Sorghum (Sorghum bicolor L.) has broad agroecological adaptability, is resistant to drought, is resistant to pests and diseases compared to other plants. The high carbohydrate content (amylose and amylopectin) of around 73 g / 100 g material from sorghum is very possible to be converted into ethanol. This study aims to determine the optimum reducing sugar concentration before and after the initial treatment by microwave and to get bioethanol with the highest levels and percent yield. A total of 10 grams of sorghum powder were suspended with an aqueous solution of H2SO4 1%, 2% and 3% as much as 250 mL and then heated using microwave irradiation at temperatures of 100, 150, 200 and 250 oC for 20, 30, and 40 minutes. The liquid fraction of hydrolysis results was analyzed by reducing sugar content by the DNS method using a UV-Vis spectrophotometer. The results of the DNS (Dinitrosalisilat) analysis showed that reducing sugar levels increased with increasing hydrolysis temperatures at 100 0C to 150 0C (2.8 - 4.4 mg / L) and decreased levels at temperatures 200 and 250 0C. The results of hydrolysis optimization with variations in concentration over 30 and 40 minutes obtained reducing sugar levels increase with increasing acid concentration at the time of hydrolysis 30 minutes ie 2.0-8.5 mg / L and experienced a significant increase when extending the hydrolysis time 40 minutes ie 19, 1-42.7 mg / L. Reducing sugar concentration for ethanol production using a temperature of 150 0C with an acid concentration of 2% at the time of hydrolysis 40 minutes which is equal to 34.3 mg / L. Bioethanol Production from Dry Soil Sorghum Waste with Initial Treatment of Microwave Irradiation.